Excited state lifetimes in the fp - shell mirror nuclei - Escudeiro, Rafael (2023)
Experimental and theoretical studies on nuclear structure aim to describe the observed phenomenology of the atomic nucleus. One of the most useful theoretical tools for the description of nuclear structure is the symmetry between protons and neutrons under the action of the nuclear force. From this symmetry arises the isospin formalism, which describes protons and neutrons as two states of the same particle, the nucleon. Conservation and breaking effects of the so-called isospin symmetry allowed the explanation of several nuclear phenomena and provided a powerful probe for the study of the nuclear force. Mirror nuclei are nuclei that have the number of protons and neutrons exchanged, resulting in an almost identical level scheme for the pair reflecting the similarities in the underlying structure. The measurement of the differences in excitation energy between isospin analogue states could advance the understanding about the structure of nuclei, starting from the f7/2 shell. Transition probabilities of mirror nuclei are, as well, an important instrument to understand how protons and neutrons contribute to the collective behavior of nuclei. In this work, two experiments are reported for the study of isospin symmetries by comparing lifetimes of excited states in nuclei in the mass region A = 50. The first experiment obtained the lifetimes of isospin analogue excited states in the mirror nuclei 47Cr-47V and 49Mn - 49Cr and was performed in the GANIL laboratory, France. The fusion-evaporation reactions that populated excited states in these nuclei were performed using a beam of 36Ar with 115 MeV bombarding a target of 0.55mg/cm2 CaO with a gold backing of 10mg/cm2. The particles emitted during evaporation were detected with the ancillary detectors DIAMANT, NEutron Detector Array - NEDA, and Neutron Wall. The gamma rays depopulating the excited states in these nuclei were detected using the Advanced GAmma Tracking Array - AGATA apparatus. The second experiment obtained the lifetime of the 6 state of the 54Ni nucleus and was performed at the RIKEN Nishina Center laboratory, Japan. In order to populate low spin states in the 54Ni nucleus, a neutron knockout reaction of an exotic beam of 55Ni on a 6mm thickness target of 9Be was performed. The 55Ni beam was produced through the fragmentation of a 78Kr primary beam with 345MeV/u on a production target, consisting in a 7mm thickness of 9Be. The 55Ni beam was separated and selected in the BigRIPS fragment separator using the TOF - Br - delta E method. The detection of gamma rays depopulating the excited states of 54Ni was performed by the Detector Array for Low-Intensity radiation DALI2+ and the identification of the 54Ni produced in the reaction was performed by the ZeroDegree spectrometer. The structure of the nuclei studied in this work was interpreted by comparison to the Large Scale Shell Model with the use of the ANTOINE code and the effective interaction KB3G, which allows the interaction of nucleons in the full fp space and includes the effects of the Coulomb interaction. From the comparison of experimental data and Large Scale Shell Model calculations, it was possible to obtain a value for the effective charges of protons and neutrons.